1985
DOI: 10.1159/000156229
|View full text |Cite
|
Sign up to set email alerts
|

How Stranger Encounters of Common Marmosets (Callithrix jacchus jacchus) Are Influenced by Family Members: the Quality of Behavior

Abstract: The initial confrontations of 33 previously unfamiliar pairs of common marmosets were observed. Four types of pairs were used (alpha males/alpha females; alpha males/subdominant females; alpha females/subdominant males; subdominant males/sub-dominant females). Each dyad was tested in five different experimental conditions: (1) isolation of both individuals from their families, unilateral encounters in which either the (2) male’s or the (3) female’s family was visible to the dyad through a one-way screen, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
57
3

Year Published

1988
1988
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 34 publications
6
57
3
Order By: Relevance
“…The observations of intrasexual aggression, combined with the finding that paired animals show more aggressive behaviors towards oppositesexed stranger when the familiar pairmate is present, suggest that common marmosets are considerably more aggressive in the presence of the familiar pairmate than they are individually (Evans 1983). However, in the absence of the pairmate, common marmoset females are indifferent to novel males, whereas males actively solicit contact and even sexual interactions with novel females (Anzenberger 1985;Evans 1983).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The observations of intrasexual aggression, combined with the finding that paired animals show more aggressive behaviors towards oppositesexed stranger when the familiar pairmate is present, suggest that common marmosets are considerably more aggressive in the presence of the familiar pairmate than they are individually (Evans 1983). However, in the absence of the pairmate, common marmoset females are indifferent to novel males, whereas males actively solicit contact and even sexual interactions with novel females (Anzenberger 1985;Evans 1983).…”
Section: Introductionmentioning
confidence: 93%
“…From several previous studies, it is known that common marmosets often behave aggressively towards opposite-sexed strangers when their own mate is present (Anzenberger 1985(Anzenberger , 1993Evans 1983;Sutcliffe 1980;Sutcliffe and Poole 1984). Furthermore, common marmosets show a high level of intrasexual aggression (Evans 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, few studies have addressed the role of sex hormones in male behavior among captive marmosets, with only a few papers examining the sexual strategies used by males to maintain social rank and reproductive position within the social group (7,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…This investigator also reported that the dominants in other captive groups of unrelated adult males had significantly higher plasma luteinizing hormone and testosterone levels, indicating that reproductive failure in males seems to depend, at least in part, on hormonal differences (16). Despite this reproductive inhibition, subordinate males may show the mounting behavior and even ejaculate (7,13). Baker et al (15), investigating a mechanism to explain the reproductive collapse of sons living in their natal groups, found that avoidance of mating with familiar and related females and possibly behavioral mechanisms of competition were involved in the inhibition since testosterone levels were similar for fathers and sons.…”
Section: Introductionmentioning
confidence: 99%